Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jhazmat.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid enhanced activation of oxygen by ferrous iron: A case of aerobic degradation of rhodamine B

Abstract: Molecular oxygen activation by ferrous ions (Fe(II)) in aqueous solution could generate reactive oxygen species (ROS) with high oxidation potential via reaction between Fe(II) and oxygen molecules (Fe(II)/air), however, ROS yielded in the Fe(II)/air process is insufficient for removal of organic pollutants due to the irreversible ferric ions (Fe(III)) accumulation. In this study, we demonstrate that ascorbic acid (AA) could enhance ROS generation via oxygen activation by ferrous irons (AA/Fe(II)/air) and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…A recent study by Huang et al (2017) confirmed the importance of the structural configuration of ascorbate on the hematite surface, and the monodentate mononuclear complex on the (012) surface led to a higher reductive dissolution rate than that of the bidentate monodentate complex on the (001) surface. The specific mechanism of ascorbate in the Fe 2+ /Fe 3+ cycle was suggested, and the reduced Fe 2+ caused molecular oxygen activation (Hou et al 2016). As a result, reactive oxygen species were generated, possibly causing the transformation of iron (hydr)oxides.…”
Section: Possible Biological Effects On the Transformation Of Iron (Hmentioning
confidence: 99%
“…A recent study by Huang et al (2017) confirmed the importance of the structural configuration of ascorbate on the hematite surface, and the monodentate mononuclear complex on the (012) surface led to a higher reductive dissolution rate than that of the bidentate monodentate complex on the (001) surface. The specific mechanism of ascorbate in the Fe 2+ /Fe 3+ cycle was suggested, and the reduced Fe 2+ caused molecular oxygen activation (Hou et al 2016). As a result, reactive oxygen species were generated, possibly causing the transformation of iron (hydr)oxides.…”
Section: Possible Biological Effects On the Transformation Of Iron (Hmentioning
confidence: 99%
“…Purification of natural water resources from organic dyes due to their resistance to decomposition processes [1] is a problem of topical interest [2][3][4][5]. Conventional treatment technologies such as biological, physical and chemical methods [6][7][8][9][10] are neither cheap nor provide the required efficiency. Recently, special attention has been paid to advanced oxidative process (AOP) technologies, the use of which allows for the decomposition of pollutants into less toxic products with the processes of destruction occurring at high rates, which is a significant advantage [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large amount of sludge disposal was created during the chemical and physical treatments [7,8-10-12] . Especially, adsorption, filtration processes did not destroy organic dyes which only incorporated them into the sludge waste [8,11,12] . On the contrary, advanced oxidation processes for the destruction of organic compounds have aroused much attractive in recent years [5,[12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%